Colab: ecologia do conhecimento em ambientes de convergência digital - Bicudo, Sergio (2007)
The present Thesis investigates of that it forms the advances in the information technologies and communication requalificaram the production of knowledge in planetary scale. It was observed, in the research process, that the purely technical development is of a humanistic perspective comes determining an increasing picture of predatory exploration, pollution, global heating, social inequality, at last, of a gamma of destructive processes unchained by a fragmented vision of the existence human being. We look for to mark out with buoys the research inserting the slight knowledge of sustainability of Fritjof Capra and ecology of Guattari, problematizing inside of an applied ecological perspective to new media environments . The main specificities of the digital ways had been systemize e, from the references of expanded media , Arlindo Machado is observed that the media languages if reverse speed-mean by means of the process of digital convergence, constituting a new matrix of forms and functionalities. In the dialogue with the estimated ones of emergency , of Steven Johnson and collective intelligence , of Pierre Levy, deep alterations in the cultural scene are observed. In this new macro environment, we could contextualizes the knowledge production, evaluating themselves systems of management of collective intelligence and verifying it application of the concepts observed in the scope of the social use for the social nets. The definition is clear of that the new hybrid formats, as the Digital Television, the Web and Mobile Devices, combine visual, sonorous and verbal languages, assuming new roles with the substantive increment of the programming resources, social data processing and nets. The media, therefore, start to be, beyond element of symbolic representation, a new space of experience human being, integrated to physical world e, as such, devoid of a sustainable model